Mechanical, dynamic mechanical and morphological properties of composites based on recycled polystyrene filled with wood flour wastes - Poletto, Matheus (Maderas. Ciencia y Tecnología, 2017)
In this work, the potential for usage recycled polystyrene and wood flour wastes as materials for development wood plastic composites was evaluated. The effects of wood flour loading and coupling agent addition on the mechanical, dynamic mechanical and morphological properties of polystyrene wood flour composites were examined. The results showed that the mechanical properties decreased with the wood flour loading. However, an improvement in composite compatibility was observed when the coupling agent was used resulting in the increase of mechanical and dynamic mechanical properties. A morphological study demonstrates the positive effect in the interfacial adhesion between filler and matrix caused by the coupling agent addition. Based on the findings of this work, both waste materials can be used for development composites with higher performance. PDF XML